Determination of isotretinoin (13-cis-retinoic acid) using a sensor based on reduced graphene oxide modified with copper nanoparticles - Fernandes, Victoria Quintas [UNESP] (2020)
The electrochemical behaviour of isotretinoin (13-cis-RA) on an electrode modified with a composite based on reduced graphene oxide (rGO) modified with copper nanoparticles (CuNPs) was investigated. The rGO-CuNPs composite was successfully synthesized by a simple chemical reduction step and then characterized by microscopic and electrochemical techniques. The rGO-CuNPs modified glassy carbon (GC) electrode was applied successfully in the direct electrochemical detection of isotretinoin in a 0.2 mol L− 1 phosphate buffer solution (PBS - pH 7.0) solution (as the electrolyte). Differential pulse voltammetry (DPV) was the methodology used. The presented method displayed linearity in the concentration range from 0.2 to 3.0 μmol L− 1 with a limit of detection (LOD) of 15.3 nmol L− 1. This is the lowest LOD for isotretinoin reported in the literature using an electroanalytical approach. The proposed sensor was applied in the determination of isotretinoin in synthetic plasmatic serum with a recovery of 91% from the original signal.